2018
DOI: 10.1101/312884
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

S100A8/A9 mediate the reprograming of normal mammary epithelial cells induced by dynamic cell-cell interactions with adjacent breast cancer cells

Abstract: To understand the potential effects of cancer cells on surrounding normal mammary epithelial cells, we performed direct co-culture of non-tumorigenic mammary epithelial MCF10A cells and various breast cancer cells. Firstly, we observed dynamic cell-cell interactions between the MCF10A cells and breast cancer cells including lamellipodia or nanotube-like contacts and transfer of extracellular vesicles. Co-cultured MCF10A cells exhibited features of epithelial-mesenchymal transition, and showed increased capacit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…These results suggest an accumulation of partially differentiated luminal secretory cells in mammary tissue from a never pregnant, post-pubescent female mouse. We found that mEC4 cells expressed higher levels of Lactalbumin Alpha (Lalba) and S100 Calcium Binding Protein A8 (S100a8) mRNAs [8,51], while those from mEC5 expressed high levels of Aldehyde Dehydrogenase 1 Family Member A3 (Aldh1a3) and Transferrin (Trf) mRNAs, all previously associated with luminal progenitor cells [27] (Fig. 2B and Supplementary Fig.…”
Section: Improving the Classification Of Mammary Epithelial Cell Populationsmentioning
confidence: 59%
“…These results suggest an accumulation of partially differentiated luminal secretory cells in mammary tissue from a never pregnant, post-pubescent female mouse. We found that mEC4 cells expressed higher levels of Lactalbumin Alpha (Lalba) and S100 Calcium Binding Protein A8 (S100a8) mRNAs [8,51], while those from mEC5 expressed high levels of Aldehyde Dehydrogenase 1 Family Member A3 (Aldh1a3) and Transferrin (Trf) mRNAs, all previously associated with luminal progenitor cells [27] (Fig. 2B and Supplementary Fig.…”
Section: Improving the Classification Of Mammary Epithelial Cell Populationsmentioning
confidence: 59%
“…Breast cancer cells can transform normal breast epithelial cells to exhibit cancerous properties, including enhanced proliferation and migration, EMT-related features, and loss of apicalbasal polarity [168]. S100A8/A9 can mediate dynamic interaction between normal breast epithelial cells and adjacent breast cancer cells to induce reprogramming [169]. Coculture with breast cancer cells or induction of overexpression of S100A8/A9 revealed that normal epithelial cells exhibit features of EMT, and the capacity of cell proliferation, migration, colony formation, and threedimensional sphere formation is increased [169].…”
Section: Breast Cancer Cells-normal Epithelial Cellsmentioning
confidence: 99%
“…It was reported that S100A8 promotes activation of mitogen‐activated protein kinase (MAPK) and NF‐κB signaling pathways in colon cancer cells (Ichikawa et al, 2011). Phosphorylated forms of mTOR and Akt were increased in S100A8‐overexpressing MCF10A cells (Jo et al, 2018). Our study suggests that CAFs upregulate S100A8 in breast epithelial cells, inducing an invasive phenotype, possibly via mTOR and/or MAPK signaling pathways.…”
Section: Discussionmentioning
confidence: 99%